Fermentation strategies for production of hyaluronic acid through biosynthesis by streptococcus zooepidemicus and recombinant escherichia coli using stirred tank bioreactor - Lai, Zee Wei (2013)
Hyaluronic acid (HA) is a high molecular mass, composed of D-glucuronic acid and N-acetyl glucosamine residues linked by β-1-3 and β-1-4 glycosidic bonds. It is a high value biopolymer due to its biological functions and unique physicochemical properties. It has wide variety applications in biomedical, healthcare and cosmetic field. The HA from rooster comb for human therapeutics carries the risk of crossspecies viral infection; thus, microbial fermentation is gradually replacing extraction as the preferred source of HA which has the advantages of low production costs and more efficient purification. In the attempt to achieve effective HA biosynthesis by a microorganism,optimization of medium formulation, development of suitable process strategies and strain improvement are required. In the present study, the experimental data from batch fermentation was analysed in order to form the basis for a kinetic model of the process. Unstructured kinetic model based on Logistic and Luedeking-piret equations was found suitable to describe the growth, substrate consumption and HA biosynthesis by S. zooepidemicus ATCC 39920 in batch fermentation using glucose as a carbon source. From the modelling, it was found that the HA biosynthesis by S.zooepidemicus ATCC 39920 was a growth-associated process. The present study was also undertaken to investigate the culture conditions and specific nutritional requirements for the growth and high molecular weight of HA biosynthesis using a stirred-tank bioreactor. Different agitation speeds (200-600 rev/min) were initially investigated using Rushton turbine impeller. The effects of glucose (20, 30, 50 and 60 g/L), nitrogen sources ((NH4)2S2O8, (NH4)2PO4, yeast extract, and tryptone) and carbon/nitrogen (C/N) ratio on the growth of the strain and on HA biosynthesis were investigated. The HA productivity and molecular weight exhibited by the strain in batch fermentations using Rushton turbine and helical ribbon impellers were compared. The potential use of n-dodecane and n-hexadecane as oxygen vectors for enhancing HA biosynthesis by S. zooepidemicus ATCC 39920 was also investigated using a 2-L stirred-tank bioreactor equipped with helical ribbon or Rushton turbine impellers. The optimum agitation speed for the HA biosynthesis (0.587 g/L) was obtained at 300 rev/min. Increasing the agitation speed would increase the oxygen transfer rate. The organic nitrogen sources (yeast extract and tryptone) were proven to be favourable used in the medium for HA biosynthesis compared to inorganic nitrogen sources. About 2.44 g/L of HA with a high molecular weight (4.36 x 106 Da) was synthesised at an optimal C/N of 5:1 (using a mixture of yeast extract and tryptone) in the bioreactor equipped with a Rushton turbine impeller. Helical ribbon impeller showed efficient mixing in a non-Newtonian HA broth. It was able to improve the HA molecular weight from 4.36 x 106 Da to 5.20 x 106 Da, even though the HA concentrations obtained are almost the same at fixed impeller tip speed (0.785 m/s) using both impellers. Batch HA fermentation with 1% (v/v) n-dodecane or 0.5% (v/v) n-hexadecane addition was carried out at different impeller tip speeds. The maximum HA concentration (4.25 g/L) and molecular weight (1.54 x 107 Da) were obtained when 0.5% (v/v) n-hexadecane and 0.785 m/s impeller tip speed of helical ribbon were used. On the other hand, biosynthesis of HA by recombinant Escherichia coli ROSETTA (DE3) harbouring has genes (B, C and D) from S. zooepidemicus ATCC 39920 previously developed in our laboratory was also investigated in batch and fed-batch fermentations. The maximum HA concentration produced by E. coli ROSETTA (DE3) was increased by about 16% in the stirred-tank bioreactor (127.00 mg/L) with a controlled dissolved oxygen tension at 30% air saturation via cascade control of airflow rate and agitation speed when compared with the shake-flask fermentation. The fed-batch fermentation with constant feeding (2 mL/min) of 10 g/L glucose was not improved neither biosynthesis nor HA molecular weight. Nevertheless, the HA molecular weight was increased by about 42% in the bioreactor experiment compared to shake-flask fermentation. Generally, the HA biosynthesis by S. zooepidemicus ATCC 39920 and E. coli ROSETTA (DE3) applying an optimal process control strategy of 2-L stirred-tank bioreactor was improved by 487.83% and 46.31%, respectively when compared with the shake-flask experiment of nonoptimal condition.